Determinan Perilaku Opurtunistik Penyusunan Anggaran Pemerintah Propinsi di Indonesia - Vivin Dwi Rizki; Maria; Sarikadarwati (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This research intends to examine the influence of Regional Original Revenue (PAD), General Allocation Funds (DAU), and Special Allocation Funds (DAK) toward Opportunistic Behavior of Budget Compilers in Provincial Governments in Indonesia. The research objects selected to be the research population are 34 provinces in Indonesia during 2017-2021. The sampling technique was selected purposively with a total sample of 25 provinces in Indonesia. The type of study data source is in the form of secondary data those are Budget Realization Reports for each Provincial Government sourced from the BPK RI and expenditure information data based on functions contained on DJPK website. Multiple linear regression analysis is used as a method of analysis by applying the IBM SPSS version 29 program. The conclusions obtained from the research indicate that partially Regional Original Revenue effects Opportunistic Behavior in Budgeting, while General and Special Allocation Fund partially have no effect on Opportunistic Behavior in Budgeting. Meanwhile, together, Regional Original Revenue, General Allocation Fund, and Special Allocation Fund influence the Opportunistic Behavior of Budgeting. This research is limited to the provincial government level and only discusses the influence of PAD, DAU, and DAK on Opportunistic Behavior in Budget Preparation within a five-year period, therefore it would be better if further research to increase the quantity and variety of samples so the scope of research is wider. Apart from that, it is hoped that future researchers will be able to use other related variables so that other factors that might cause opportunistic behavior can be identified.